Anti-natalism as a recipe for modern problems? - Jach, Filip (Hybris, 2017)
The paper is an attempt to bring nearer the central assumptions of the anti-natalist thought and thus to answer the question whether anti-natalism could be a solution to the problems of contemporary world. In order to achieve this, the roots of the movement, which stem from Eastern philosophy, are presented. Then, certain types of anti-natalism are examined. In the process the sources of inspiration for analysed thought are traced back to the philosophical and religious pessimisms, but it also becomes clear that anti-natalism displays many more inspirations both from western and eastern intellectual traditions. Next, the arguments for anti-natalism are presented and at the end of the paper it is argued, while answering the eponymous question, that anti-natalism view needs some modifications or must be interpreted in a certain way in order to render it helpful in solving our present-day problems.